The fluroxene mediated degradation of cytochromes P-450 - Bradshaw, Jennifer Jean (Division of Medical Biochemistry, 2020)
The degradation of cytochromes P-450 by fluroxene (2,2,2-trifluoroethyl vinyl ether) has been investigated. Fluroxene is shown to specifically degrade cytochromes P-450 in vivo and in vitro without affecting the levels of the other microsomal enzymes, cytochrome ~S a.nd NADPH-cytochrome~ reductase. Fluroxene appears to degrade the haem moiety of cytochromes P-450 but does not affect the level of the apoprotein. The degradation of cyto-chromes P-450 by fluroxene is accompanied by a loss of E-nitroanisole 0-demethylase and biphenyl 4-hydroxylase activities and a decrease in the extent of aniline binding is observed. By using cytochromes P-450 dependent reactions which are catalysed by specific type P-450 cytochromes,~.~· the hydroxylation of benzpyrene, the N-demethylation of ethyl-morphine and the binding of ethyl isocyanide, it is established that only cytochrome P-450 is degraded by fluroxene in vivo following phenobarbital induction of animals, and both cytochrome P-450 and cytochrome P-448 following methylcholanthrene induction. The same type P-450 cytochromes are shown to be degraded by fluroxene in vitro in phenobarbital and methylcholanthrene induced microsomes. This was established from studies of the kinetics of the fluroxene mediated degradation of cyto-chromes P-450. In addition, the K values for the flurox-m ene mediated degradation of cytochromes P-450 differ with iii the different inducing agents and indicate the involve-ment of two different type P-450 cytochromes in the degradation reaction in methylcholanthrene induced micro-somes. Metabolic activation of cytochromes P-450 by the cyto-chromes P-450 drug metabolising pathway appears to be essential for the fluroxene mediated degradation of cyto-chromes P-450. Since none of the known or proposed metabolites of fluroxene can mimic the degradation of cytochromes P-450 by fluroxene, a reactive species is proposed to be involved. By varying the experimental conditions, and with the use of inhibitors of cytochromes P-450, the likely sequence of events in the fluroxene mediated degradation of cytochromes P-450 is shown to be as follows: fluroxene is metabolised by cytochrome P-450 to a transient reactive intermediate which has the ability to degrade the haem moiety of cytochrome P-450 and cyto-chrome P-448. By comparing the ability of various analogues of fluroxene to degrade cytochromes P-450, it is established that the formation of the proposed reactive intermediate is dependent on the presence of the vinyl moiety of the molecule. Initial studies indicate that the reactive species may take the form of an epoxide.